Profitability Analysis of Selected Companies in the Sugar Industry in India Based on their Margin on Sales - Umarani, R.; Nithya, G. (Indian Journal of Finance, 2013)
Sugar is made from sugarcane, which was arguably discovered thousands of years ago in New Guinea. From there, the route was traced to India and Southeast Asia. It was India which began producing sugar following the process of pressing sugarcane to extract its juice and boil it to get crystals. A business needs profit not only for its existence, but also for expansion and diversification. The investors want an adequate return on their investments, workers want higher wages, creditors want higher security for their interest and loan, and so on. The objective of this study is to analyze whether the overall profitability of the selected companies in the Sugar industry depends on their age, size, and region to which the company belongs based on their margin on sales. From the analysis, it was found that the southern region companies had a higher profitability than the northern region companies, and the companies having paid-up share capital less than ` 26 crores and greater than ` 26 crores had, on an average, the same amount of profitability, and the three groups of companies based on their age - new, moderate, and old - had, on an average, the same level of profitability in terms of margin on sales. It is suggested that to increase their profitability, the companies need to effectively monitor and control their expenses and effectively use their by-products. The companies can also adopt a framework for monitoring the profitability at all levels.